Exploring the effects of question generation instruction on attitudes and strategy uses in and out of the classroom. (3rd July 2021) - Shinogaya, Keita
ABSTRACT: This study explored effects of question generation instructions on students' attitudes towards question generation and strategy use. Three hundred seventy-four Japanese college students in two psychology classes participated in lectures after a pre-lecture preparation time and completed questionnaires on attitudes towards question generation and learning strategy use in and outside the classroom. Students in the "instruction group" were instructed on how to develop questions during lecture preparation to better understand the upcoming lecture. In the "connecting group", in addition to instruction, the questions students generated during preparation were linked to lecture content. The results showed that instruction significantly decreases students' perception of difficulty regarding question generation and increases learning outside the classroom. The result also suggested that connecting questions to lecture content increased students' use of micro-understanding focused strategies during preparation and increased positive attitudes towards question generation of students who did not place importance on meaningful learning.